Selection of the optimum locations for rainwater harvesting in arid regions using WMS and remote sensing. Case Study: Wadi Hodein Basin, Red Sea, Egypt - Marwa M. Aly; Sameh A. Sakr; Mohamed S.M. Zayed (Alexandria Engineering Journal, 2022)
Rainwater harvesting (RWH) strategy is one of the most effective solutions for water scarcity problem in arid and semi-arid regions. This solution is vital in achieving residents stability and helping the decision makers toward the development of such regions. The lack of measured hydrological data represents the main challenge achieving this strategy. Integration between watershed modelling and remote sensing was used as a technique to overcome this challenge. Weighted spatial probability model (WSPM) was used in classification of RWH potentiality of the sub-basins inside Wadi Hodien in the eastern desert. The results showed that WH is categorized as moderate RWH potentiality. In addition, the analysis revealed that basin slope and volume of annual flood parameters have the higher effect on the selection of the RWH sites in WH. The research also give the ability to determine the most suitable locations for RWH through the presented integrated models without the need of hydrological measurements data.